2021
DOI: 10.3389/fvets.2021.691853
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Endoparasites in Adult Swedish Dogs: A Coprological Investigation

Abstract: The occurrence of endoparasites in Swedish adult dogs (n = 303) was investigated between January and October 2014. Included dogs had to be clinically healthy, older than 1 year and untreated with anthelmintics or endectocides for at least 3 months prior to sampling. They were grouped according to age, category of dog and time since last antiparasitic treatment. Samples were analyzed by flotation to detect parasitic eggs and cysts/oocysts. Among these, 129 (43%) dogs were also analyzed with the Baermann-techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…All dogs positive for taeniid eggs were living in rural areas, indicating that contact with wildlife or livestock animals increases the risk of patent taeniid infection by dogs (Grandi et al 2021 ; Waindok et al 2021 ). This is supported by a previous study regarding wild gray wolves in Lower Saxony (Germany), where Taeniidae were found as the second most prevalent parasites (21.74%) (Bindke et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…All dogs positive for taeniid eggs were living in rural areas, indicating that contact with wildlife or livestock animals increases the risk of patent taeniid infection by dogs (Grandi et al 2021 ; Waindok et al 2021 ). This is supported by a previous study regarding wild gray wolves in Lower Saxony (Germany), where Taeniidae were found as the second most prevalent parasites (21.74%) (Bindke et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, such helminthoses are rare in the form of mono-infections. The main component of co-infections is usually Toxocara (T.) canis (W e r n e r, 1782) in puppies or young dogs and Trichuris (T.) vulpis (F r o e l i c h, 1789) in adult dogs [10,14,31,48]. Other members of helminthic parasitocenoses in dogs are usually Toxascaris (T.) leoninа (L i ns t o w, 1902), representatives of Ancylostomatidae family-Uncinaria (U.)…”
Section: Introductionmentioning
confidence: 99%